On English Pygmies and Giants: the Physical Stature of English Youth in the late-18th and early-19th Centuries - John Komlos (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2005)
The physical stature of lower- and upper-class English youth are compared to one another and to their European and North American counterparts. The height gap between the rich and poor was the greatest in England, reaching 22 cm at age 16. The poverty-stricken English children were shorter for their age than any other European or North American group so far discovered, while the English rich were the tallest in their time: only 2.5 cm shorter than today's US standards. Height of the poor declined in the late-18th century, and again in the 1830s and 1840s conforming to the general European pattern, while the height of the wealthy tended rather to increase until the 1840s and then levelled off.
urn:nbn:de:bvb:19-epub-573-3
Keywords: N33; N53; N93; 330; Height; Biological Standard of Living; Anthropometry; Inequality; Industrial Revolution